The effect of the dibenzylbutyrolactolic lignan (-)-cubebin on doxorubicin mutagenicity and recombinogenicity in wing somatic cells of Drosophila melanogaster - de Rezende, A. A. A.; Silva, M. L. A. E.; Tavares, D. C.; Cunha, W. R.; Rezende, K. C. S.; Bastos, J. K.; Lehmann, M.; de Andrade, H. H. R.; Guterres, Z. R.; Silva, L. P. [UNESP]; Spano, M. A. (Pergamon-Elsevier B.V. Ltd, 2011)
The dibenzylbutyrolactolic lignan (-)-cubebin was isolated from dry seeds of Piper cubeba L (Piperaceae). (-)-Cubebin possesses anti-inflammatory, analgesic and antimicrobial activities. Doxorubicin (DXR) is a topoisomerase-interactive agent that may induce single- and double-strand breaks, intercalate into the DNA and generate oxygen free radicals. Here, we examine the mutagenicity and recombinogenicity of different concentrations of (-)-cubebin alone or in combination with DXR using standard (ST) and high bioactivation (HB) crosses of the wing Somatic Mutation and Recombination Test in Drosophila melanogaster. The results from both crosses were rather similar. (-)-Cubebin alone did not induce mutation or recombination. At lower concentrations, (-)-cubebin statistically reduced the frequencies of DXR-induced mutant spots. At higher concentrations, however, (-)-cubebin was found to potentiate the effects of DXR, leading to either an increase in the production of mutant spots or a reduction, due to toxicity. These results suggest that depending on the concentration, (-)-cubebin may interact with the enzymatic system that catalyzes the metabolic detoxification of DXR, inhibiting the activity of mitochondria! complex 1 and thereby scavenging free radicals. Recombination was found to be the major effect of the treatments with DXR alone. The combined treatments reduced DXR mutagenicity but did not affect DXR recombinogenicity. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Somatic Mutation and Recombination Test; SMART; Toxicity; Cyp6A2